On the Variation of Intercalation Voltage in Si-doped (Na3+yV2(PO4)3-y(SiO4) y) Cathode Material: A First-Principles Study - Scientika, Qory Cipta; Wella, Sasfan Arman; Fathurrahman, Fadjar; Nuruddin, Ahmad; Anshori, Isa; Sakti, Aditya Wibawa; Shukri, Ganes (Journal of physics. Conference series, 2025)
The Na 3 V 2 (PO 4 ) 3 (i.e. NVP) is a Natrium Super-ionic Conductor (NaSICON) type compound which provides a 3D open framework that has strong covalent bonds, making this material a promising cathode material with high-power density. Increasing its ability to deliver Sodium-ion at a faster rate and at a higher electronic conductivity have been becoming target researches for its further utilization. Here, by utilizing the first-principles calculation, we investigated the effect of partial substitution of P with Si on the intercalation voltage of silicon-doped NVP. We determine the thermodynamically stable phase of the pristine NVP and Si-doped NVP or Na 3.1 V 2 (PO 4 ) 2.9 (SiO 4 ) 0.1 (i.e. NVPS0.1) by considering various sodium configurations. Based on the mixing energy results, we then calculated the intercalation voltage and found that the addition of Si dopant slightly increases the range of intercalation voltage of pure NVP from 1.43-2.36 V, ΔV = 0.93 V and 1.24-2.44 V for NVPS0.1 with ΔV = 1.20 V, increases 0.27 V. In general, our finding shows the potential of Si to modulate the overall intercalation voltage window of a NVP-based cathode material for Na-ion battery.